65.6k views
3 votes
This equation has one solution. 5(x – 1) + 3x = 7(x + 1) What is the solution?

2 Answers

2 votes

Answer:

x = 12

Explanation:

Distribute the parenthesis on both sides of the equation

5x - 5 + 3x = 7x + 7

8x - 5 = 7x + 7 ( subtract 7x from both sides )

x - 5 = 7 ( add 5 to both sides )

x = 12


User BeardedInBinary
by
5.0k points
4 votes
Open up the brackets

5x - 5 + 3x = 7x + 7
Collect like terms

5x + 3x - 7x = 7 + 5
Simplify

8x -7x = 12

x = 12
Therefore, your answer is 12.
User Gaurav Ghate
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.